Hydrodynamics, mass transfer, and yeast culture performance of a column bioreactor with ejector - Prokop, A; Janík, P; Sobotka, M; Krumphanzl, V (Biotechnology and bioengineering, 1983)
A bubble column fitted with an ejector has been tested for its physical and biological performance. The axial diffusion coefficient of the liquid phase in the presence of electrolytes and ethanol was measured by a stimulus-response technique with subsequent evaluation by means of a diffusion model. In contrast to ordinary bubble columns, the coefficient of axial mixing is inversely dependent on the superficial air velocity. The liquid velocity acts in an opposite direction to the backmixing flow in the column. The measurement of volumetric oxygen transfer coefficient in the presence of electrolytes and ethanol was performed using a dynamic gassing-in method adapted for a column. The data were correlated with the superficial air and liquid velocities, total power input, and power for aeration and mixing; the economy coefficient of oxygen transfer was used for finding an optimum ratio of power for aeration and pumping. Growth experiments with Candida utilis on ethanol confirmed some of the above results. Biomass productivity of 2.5 g L(-1) h(-1) testifies about a good transfer capability of the column. Columns fitted with pneumatic and/or hydraulic energy input may be promising for aerobic fermentations considering their mass transfer and mixing characteristics.